1984
DOI: 10.1080/00268978400102421
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic spectra ofU4+in octahedral crystal fields

Abstract: Excitation of Cs2ZrBr6 : UBr62-using 647.1 nm laser radiation initially populates the (1D~)F5 vibronic sideband. Rapid radiationless decay to the (tG4)I~ 1 and (3//6)1' s levels is followed by luminescence from these levels. In addition to the transitions to the (3//4)1" 1 ground state, transitions to the (3H4)r 4 and I" 3 components are observed in the region above 880 nm, enabling these states to be located for the first time, at 877 cm -1 and 1192 cm -1 above the ground state. Each of the electronic transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…A comparison of the electronic spectra of U 4+ ions in crystals of ThBr 4 , ZrSiO 4 , CaF 2 , etc. [16][17][18][19] shows that there is no correlation between the field parameters of one crystal (e.g., ThBr 4 ) and the analogous characteristics of another (ZrSiO 4 ). Experimental Technique.…”
Section: Introductionmentioning
confidence: 95%
“…A comparison of the electronic spectra of U 4+ ions in crystals of ThBr 4 , ZrSiO 4 , CaF 2 , etc. [16][17][18][19] shows that there is no correlation between the field parameters of one crystal (e.g., ThBr 4 ) and the analogous characteristics of another (ZrSiO 4 ). Experimental Technique.…”
Section: Introductionmentioning
confidence: 95%
“…In the first paper in this series [1], we reported the 647-1 nm excited luminescence spectrum of Cs~ZrBr 6 : UBr62-. The experimental measurements enabled us to locate the I~4 and 1~3 components of the 3Ha term, which lie at 877 cm -1 and 1192 cm -1 respectively above the Pz ground state.…”
Section: Introductionmentioning
confidence: 98%
“…The Cs 2 GeF 6 :U 4+ crystalgaps ͑indicated in Table II 42,43 showed that multiphonon relaxation dominates the radiative process when the energy gap below the electronic level is less than four quanta of the highest-frequency phonon coupled to the lattice, i.e., 800 cm −1 for ͑UBr 6 ͒ 2− ; they observed luminescence from those levels located above energy gaps of four to seven quanta. The application of this empirical rule to our results in Cs 2 GeF 6 :U 4+ sets the limit of smallest energy gap, that favors radiative emission, to 4¯a 1g = 2250 cm −1 , which suggests that 12T 2g , 11T 2g , and 2E g might be luminescent levels in this material.…”
Section: -5mentioning
confidence: 99%
“…In effect, given the shift of levels to higher energies, commented above, and assuming that our T e values could be calculated some 1500 cm −1 too high in the 19 436 cm −1 energy region, the green absorption could excite 5f 2 vibronic levels around the 7T 1g and 9T 2g origins, far below the first stable high energy level 11T 2g ͑Table II͒. In any case, after the first excitation and as a consequence of the lack of large energy gaps, nonradiative decay should dominate 42,43 and should occur down to the 2E g state. From this low energy level, a second green-photon absorption could only lead to low intensity, dipole-forbidden 5f 2 → 5f 2 excitation to 9T 1g or lower levels, which would decay again, nonradiatively, to 2E g ͑Table II͒.…”
Section: Quenching Of Green-to-blue Up-conversion Luminescence In mentioning
confidence: 99%
See 1 more Smart Citation